Sjukdomsresistens eller sjukdomstolerans inom husdjursaveln - en jämförelse - Burri, Stina (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2012)
Tolerance and resistance are two different defence mechanisms within the immune system that differ from each other in many ways: However it is not clear which of the two is the most advantageous in dairy production. Resistance is described as the ability to fight a pathogen in a host. Tolerance is, on the other hand, not aggressive to the pathogen per se, but rather protects the host and its tissues. Furthermore tolerance rather offsets the toxin from, for example, a parasite whilst resistance offsets the parasite itself. Resistance is however disease specific, which means breeding for a large number of diseases is needed in order to make resistance worth the cost for the host. Tolerance is on the other hand not disease specific. Thus, it would, in theory, be more sustainable to choose tolerance for immune mechanism in domestic animal breeding. Yet more research in disease tolerance is needed in order to persuade researchers it has an advantage over disease resistance, research that is both costly, ethically problematic, and needs an incredible amount of animal material.